Consideraciones en torno a los términos etruscos papa y teta y sus relaciones isonómicas con el latín - López Montero , Roberto (Cuadernos de Filología Clásica. Estudios Latinos, 2010)
In this paper, we analyze the semantic difficulty that exists in the etruscan terms papa and teta and their morphologic derivatives papals/ś and tetalś/z. the latter binomial is translated, respectively, as ‘that of the grandfather’ and ‘that of the grandmother’, whereas the meaning of papa and teta seems not to be, a prori, that of ‘grandfather’ / ‘grandmother’. the isonomic comparison with the Latin terms pappus and pap(p)a can offer a sketch of solution.